Blockchain Technology as an Alternative Method of Payment Transaction Proof - Bambang Irawan (Publisher Cv. Inara, 2021)
Today, the development of information technology allows all needs in the payment system to conduct safely and reliably with the support of blockchain technology. Blockchain technology is currently a concept getting more attention in financial technology (Fintech). This technology combines several computer technologies, including distributed data storage, point-to-point transmission, consensus mechanisms, and encryption algorithms often referred to as cryptography. Currently, various payment methods are available, Direct payment methods via the website, credit cards, automatic debit (Autopay), Mobile / Internet Banking, Non-bank, E-commerce, and E-wallet. All of the above payment systems still require a third party as a guarantor for the transactions made. Another problem that arises is a notification of bill dues to consumers, using conventional media in letters, emails, and notices of short message service (SMS), which allows consumers to miss the given deadline. It could cause the service to terminate. Blockchain technology is currently still considered an innovation that disrupts the world of banking and the internet. However, because this technology is a breakthrough major in data storage and information transmission, it will fundamentally change the global financial and economic operating model towards new technologies and industrial transformation in the financial industry. Current consumer bill payment methods use conventional banking systems, and notification systems for payment deadlines are less efficient; we propose a payment system with blockchain technology and the internet of things (IoT) to solve the current problem.